2013
DOI: 10.1017/s0007114512005594
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of naringenin against experimental colitis via suppression of Toll-like receptor 4/NF-κB signalling

Abstract: Naringenin, one of the most abundant flavonoids in citrus, grapefruits and tomatoes, has been used as a traditional anti-inflammatory agent for centuries. However, the molecular mechanism of naringenin in intestinal inflammation remains unknown so far. The present study investigated a molecular basis for the protective effect of naringenin in dextran sulphate Sodium-induced murine colitis. Pre-administration of naringenin significantly reduced the severity of colitis and resulted in down-regulation of pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 47 publications
13
118
0
3
Order By: Relevance
“…[21][22]27 At present, TLR4/ NF-κB pathway has been believed as a targets for IBD control. 28 The results of this study demonstrated that CHOS treatment significantly downregulated the enhanced expression of TLR4 and NF-κB induced by LPS, suggesting the possible involvement of this signal pathway in the protective role of CHOS against IBD. Interestingly, although IL-8 was also a pro-inflammatory cytokine involved in IBD, 18 CHOS treatment appeared to have no obvious effect on LPS-induced IL-8 production of IECs in this study.…”
Section: Discussionmentioning
confidence: 54%
“…[21][22]27 At present, TLR4/ NF-κB pathway has been believed as a targets for IBD control. 28 The results of this study demonstrated that CHOS treatment significantly downregulated the enhanced expression of TLR4 and NF-κB induced by LPS, suggesting the possible involvement of this signal pathway in the protective role of CHOS against IBD. Interestingly, although IL-8 was also a pro-inflammatory cytokine involved in IBD, 18 CHOS treatment appeared to have no obvious effect on LPS-induced IL-8 production of IECs in this study.…”
Section: Discussionmentioning
confidence: 54%
“…This substance and other flavonoids are credited with antioxidative and anticarcinogenic activity. Naringenin is a flavonoid of the flavanone subclass, found mainly in citrus fruits (Dou et al, 2013), with a beneficial antioxidative and neuroprotective effect (Raza et al, 2013). Among these, the flavonoids catechin and quercetin were also found in plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were monitored daily for body weight, diarrhea, and bloody stool. Bloody diarrhea event was assessed as described before (3,4). Following measurement of the colon length, the distal colon was taken and fixed in 10% (wt/vol) buffered formalin for H&E staining.…”
Section: Methodsmentioning
confidence: 99%
“…Lubbad et al (23) have reported that amelioration of TNBS-induce colitis by curcumin is mediated through TLR4-linked NF-B inhibition. We recently demonstrated that naringenin ameliorates DSS-induced colitis via transecting TLR4/NF-B signaling cascades (4). In addition, TLR4 is indicated to be linked with MAPK pathway in IBD.…”
mentioning
confidence: 99%